Early-stage assessment of drying shrinkage in Portland limestone cement concrete using nonlinear ultrasound. (1st August 2022) - Kim, Gun; Kurtis, Kimberly E.
Highlights: This paper presents a proof-of-concept evaluation of the durability of OPC and PLC concretes in terms of the microcracking development. SHG technique is employed to investigate the role of limestone in the dimensional stability under the condition of drying shrinkage. β, strain, and mass are measured to quantitatively assess the early‐stage microcracking development in both PLC and OPC concretes. This paper demonstrates the potential of the SHG method for monitoring early-stage damage evolution in both OPC and PLC concretes. Abstract: Second harmonic generation (SHG), a nonlinear ultrasonic technique, holds great promise for reliable structural health management owing to its nondestructive detection of early-stage damage evolution in cement-based materials. Utilizing the SHG technique, this study focuses on elucidating the contribution of limestone to dimensional stability under drying shrinkage in cement-based materials. Specifically, the acoustic nonlinearity parameter β obtained from the SHG is used, together with uniaxial strain and mass reduction, to characterize the microstructural condition near the surface (∼50 mm) of Portland limestone cement (PLC, Type IL) concrete, which is compared to ordinary Portland cement (OPC, Type I/II) concrete. In both PLC and OPC specimens, β increases remarkably compared with other measured parameters (i.e., change in mass, strain). This demonstrates the sensitivity of this approach to the microstructural modification caused by drying shrinkage, allowing for the discrimination in performance of PLC and OPC.